The Determinants of Beef Cattle Market Participation on Beef Cattle Producers’ Welfare: A Case Study of West Shewa Zone, Oromia Region, Ethiopia - Bultossa Terefe Willy; Amsalu Bedemo Beyene; Daniel Masresha Amare (Advances in Agriculture)
Due to their ability to produce meat, milk, leather, glue, gelatin, and other products that people may utilize, beef cattle are domesticated. Beef cattle production and marketing play a vital role in the growth and development of the globe and the African economy. Ethiopia has great potential for livestock population in Africa and in the world but earns less from beef cattle production and marketing. Ethiopian farmers are reluctant to beef cattle market participation. Their reluctant to participate in beef cattle marketing causes lack of beef cattle products in the market and causes high prices for beef cattle and its products. The research objective was to analyze the impact of beef cattle market participation on the welfare of beef cattle smallholder farmers in Ethiopia. The primary data come from 400 randomly selected beef cattle farmers involved in beef cattle production and marketing and actors. Descriptive statistics and inferential statistics propensity score matching (PSM) model have used to analyze the collected data. The data analysis result indicated that smallholder beef cattle farmers participating in beef cattle marketing and farmers’ annual per capita consumption expenditure (economic welfare) increased by 84% more than the nonbeef cattle market participants. We assume this is a first result and investigation in the study area. The research study is important for farmers, policymakers, researchers, and the academia in general. Providing education and training, promoting the participation of more women in beef cattle marketing, and promoting and encouraging more full-time beef cattle farmers are suggested recommendations.